2021
DOI: 10.20525/ijrbs.v10i3.1112
|View full text |Cite
|
Sign up to set email alerts
|

The influence of working environment to employee performance mediated by work motivation

Abstract: This study examines the effect of work environment on retail store employee performance in Malang, Indonesia with the role of work motivation as a mediation. Respondents in this study used 152 respondents who were millennials employees of retail stores in Malang Indonesia. This study uses a statistical analysis of the Structured Equation Model and Partial Least Square. WarpPLS is used as a data processing program for hypothesis testing. The test results show that the work environment has a significant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
3
2
0
Order By: Relevance
“…Similarly, the research led by Sadewo et al (2021) supports previous research that states that inspiration (2021) has a positive and great impact on the implementation of workers and, in this concentrate, also states that inspiration is the main component that influences representative implementation.…”
Section: Indirect Influence Test Results With Sobel Testsupporting
confidence: 79%
“…Similarly, the research led by Sadewo et al (2021) supports previous research that states that inspiration (2021) has a positive and great impact on the implementation of workers and, in this concentrate, also states that inspiration is the main component that influences representative implementation.…”
Section: Indirect Influence Test Results With Sobel Testsupporting
confidence: 79%
“…They opined that a good work environment is a perfect attraction for employees and positively impacts their performance. However, their study's results supported previous findings and revealed that employee performance is directly influenced by the work environment (Sadewo et al, 2021).…”
Section: The Impact Of the Work Environment On Job Performancesupporting
confidence: 84%
“…Furthermore, these results illustrated the significant impact of job resources on nurses' job performance, even when rated by the supervisor (Bhatti et al, 2018). Contrary to most of the studied literature, Sadewo et al (2021) conducted a quantitative study among 152 employees of retail stores, and the authors examined the effect of the work environment on retail store employee performance in Malang Indonesia. Their research problem was the lack of employees on the one hand and poor employee performance on the other.…”
Section: The Impact Of the Work Environment On Job Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Mohamed and Gaballah (2018) found a statistically significant positive relationship between work climate and nurses' job performance. In the same context, Sadewo et al (2021) supported previous findings and revealed that employee performance is directly influenced by the work environment (Sadewo et al, 2021). Similarly, in Turkish study by Sarıköse and Göktepe (2022) confirm this, arguing that the nursing work environment is among the crucial factors affecting nurses' job performance.…”
supporting
confidence: 77%